Analisis Beta Saham Sektor Properti Sebelum dan Selama Krisis Ekonomi dengan Metode Time Series Auto Correlation Model - Herry Yulistyono (Jurnal Ilmiah Aset, 2008)
The main objective of this research was to know income statement ratio variable that influenced to systematic risk (Beta Saham) of the property sector previous monetary crisis and during monetary crisis took place in Indonesia. The research applied sixteen cross-section and four time series data and chose with purposive sampling. The selection of the best model used stepwise regression and analysis of research was used time-series autocorrelation method. The result of liquidity ratio ( CATA ) and capital market ratio (EPS) were consistent with apriority expectation. However, contrary to a priori expectation or not consistent with systematic risk (β) were leverage ratio (TDE) and profitability ratio (ROI). Then, the result of dummy variable was indicated consistent with hypothesis. That mean was systematic risk when accured of monetary crisis obviously and significantly different with systematic risk when accured of monetary crisis in Indonesia.